2010
DOI: 10.1016/j.quaint.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Solo man in question: Convergent views to split Indonesian Homo erectus in two categories

Abstract: Between the famous Man of Java and the new star of paleoanthropology id est the Man of Flores, embedded in the bank of the river Solo or in the shadow of the volcanoes of Sangiran, Homo erectus remains apart. Driven from evolved Homo erectus to archaic Homo sapiens, for a long time Solo man did not find a real place in taxonomy and in the scientific debate, whereas Neandertal is still famous for its cultural or biological struggle against the ancestors of modern humans. Are there two human evolutionary trends:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
1
17
0
3
Order By: Relevance
“…He attributed this combined pattern to geographic and genetic isolation of these populations on Java. In contrast, analysis of vault shape via 3D landmarks demonstrated distinct neurocranial shape in the Sambungmacan/Ngawi, Ngandong, and Trinil/ Sangiran groups, and the differences among them were non-linear (Baab, 2010;Zeitoun et al, 2010). At least some of the differences between the early Indonesian and the Ngandong fossils appear to relate to the increased size of the latter Baab, 2016b).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…He attributed this combined pattern to geographic and genetic isolation of these populations on Java. In contrast, analysis of vault shape via 3D landmarks demonstrated distinct neurocranial shape in the Sambungmacan/Ngawi, Ngandong, and Trinil/ Sangiran groups, and the differences among them were non-linear (Baab, 2010;Zeitoun et al, 2010). At least some of the differences between the early Indonesian and the Ngandong fossils appear to relate to the increased size of the latter Baab, 2016b).…”
Section: Introductionmentioning
confidence: 80%
“…It was demonstrated that Asian, along with numerous African and Georgian fossils assigned to H. erectus, were distinct from or displayed minimal overlap with other archaic Homo species on the basis of threedimensional (3D) neurocranial shape (Zeitoun et al, 2010;Baab, 2016b). There is substantial variation within this sample that spans three continents and more than a million years of evolutionary change.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations